Financial Performance Analysis of Local Government: A Case Study on Karanganyar Regency - Kusumawardani, Adelita Faraulia; Asrihapsari , Andi (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study is to analyze the financial ratios of the Karanganyar Local Government Budget Realization Report for the 2017-2022 fiscal year, with a quantitative descriptive method at the Local Finance Agency (BKD) of Karanganyar Regency. Data were sourced from the budget realization reports, scientific articles, and interviews.   Data were collected through document analysis and interviews. The components analyzed include the financial independence ratio, financial growth ratio, effectiveness ratio of original local government revenue (PAD), and local financial efficiency ratio. This study has found a low financial independence ratio of an average of 23.62%. The average PAD growth ratio was 5.14%, local income was 1.98%, operational expenditure was 1.80%, and capital expenditure was 3.72%. The PAD effectiveness ratio was classified as very effective with an average of 107.22%, and the financial efficiency ratio showed a moderate level with an average of 87.17%. This study concludes that the financial performance of the Local Government of Karanganyar Regency needs to be improved. The researchers recommend the government diversify sources of income, evaluate project management, and utilize information technology. Thus, this study provides guidance for the Local Government of Karanganyar Regency in improving the local financial performance.